Control biológico en la fase de competencia y recuperación en un triatleta - Pérez, Delia; Rangel Colmenero, Blanca Rocío; Hernández Cruz, Germán; Aguirre Zuazua, Hugo; Chávez, Estrella (ECORFAN, 2014)
The main objective of the biological control of training is to improve the design of workloads by coaches in order to prevent the adverse effect that involves the practice of high performance sport. In the present study biomarkers such immune response, heart rate variability (HRV), creatine kinase (CK), lactate and urea were measured to describe the behavior in a competition and during the recovery period. The results obtained during the evaluation provide enough information to use them as a custom control of physical activity.